GENERALIZED CONTRACTIVE MAPPINGS IN b-METRIC SPACES - Alinejad, Z.; Mirmostafaee, K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
We will apply a new method to generalize some fixed point theorems for a special class of contractive type mappings in complete b-metric spaces. We also discuss about the existence of a unique fixed point for a family of self mappings. Our results enable us to generalize some known fixed point theorems in the literature. Finally, we present some applications of our results